Investigation of Bending Behavior of Sandwich Plates Reinforced with Arched Structure - Kaveloğlu, Serdar (Fırat University, 2025)
Sandwich composite structures are used in many industrial fields, including automotive, aircraft, train, yachting, construction, and solar panels. Historically, arched structures (with an open-ended arch geometry) have been used to increase load-carrying capacity in bridges constructed from materials such as stone, wood, metal, and concrete, used for various purposes such as pedestrian, vehicle, or railway bridges. The aim of this study is to apply the superior load-carrying properties of arched structures to sandwich composite plates, thereby increasing the structure's resistance under bending. The bending strength of sandwich composite structures, created by placing carbon fiber-reinforced polymer (CFRP) composites between two complementary arch-shaped parts produced with a 3D printer, was investigated. The interiors of the sandwich composites were fabricated using a 3D printer using acrylonitrile butadiene styrene (ABS) filament, with one side flat and the other side in an arch geometry of varying widths. CFRP composite plates were used for the upper and lower surfaces of the sandwich structures. The study investigated the flexural strength of sandwich structures reinforced with arches of 0.5 mm and 1 mm thicknesses, with arch widths of 50 mm, 100 mm, and 150 mm. The results showed that the arched structures increased the flexural strength of the sandwich plates. A significant increase of 34% and 67% in maximum bending force was obtained in samples with 0.5 mm and 1 mm arch thickness and 150 mm arch width, respectively, compared to structures without arches.

Sandviç kompozit yapılar otomotiv, uçak, tren, yatçılık, inşaat ve güneş panelleri gibi birçok endüstriyel alanlarda kullanılmaktadır. Geçmişten günümüze kadar taş, ağaç, metal ve beton gibi malzemelerden farklı amaçlarla yaya, taşıt ya da demir yolu olarak kullanılan köprülerde yük taşıma kapasitesini artırmak amacıyla kemerli (iki ucu açık yay geometrisinde) yapılar kullanılmıştır. Bu çalışmanın amacı, kemerli yapıların üstün yük taşıma özelliğini sandviç kompozit plakalara uygulamak ve bu sayede yapının eğilme altındaki dayanımını artırmaktır. 3 boyutlu yazıcı ile üretilen ve birbirini tamamlayan kemer geometrisine sahip iki parça arasına, kemer işlevi görecek şekilde karbon fiber takviyeli polimer (CFRP) kompozitler yerleştirilerek oluşturulan sandviç kompozit yapıların eğme dayanımları incelenmiştir. Sandviç kompozitlerin iç kısımları üç boyutlu yazıcıda akrilonitril bütadien stiren (ABS) filamentten bir yüzü düz, diğer yüzü farklı genişliklerde kemer geometrisinde üretilmiştir. Sandviç yapılarda alt ve üst yüzeyler CFRP kompozit plakalar kullanılmıştır. Çalışmada 50 mm, 100 mm, 150 mm kemer genişliğinde 0,5 mm ve 1 mm kemer kalınlığındaki kemerlerle güçlendirilmiş sandviç yapıların eğme dayanımları incelenmiştir. Sonuç olarak, kemerli yapılar sandviç plakaların eğme dayanımlarını artırdığı tespit edilmiştir. 150 mm kemer genişliğindeki 0,5 mm ve 1 mm kemer kalınlığına sahip numunelerde kemersiz yapılara göre maksimum eğme kuvvetinde sırasıyla %34 ve %67 oranında önemli bir artış elde edilmiştir.
Kemerli Yapıyla Güçlendirilmiş Sandviç Plakaların Eğme Davranışlarının İncelenmesi
Keywords: Solid Mechanics; Katı Mekanik; Composite and Hybrid Materials; Kompozit ve Hibrit Malzemeler